Study of adhesin from Aggregatibacter actinomycetemcomitans local isolate on alveolar bone destruction in aggressive periodontitis disease - Rini Devijanti Ridwan; Tuti Kusumaningsih; Sidarningsih Sidarningsih; Soetjipto Soetjipto (The East Java Biological Society, 2016)
Adhesion is a powerful survival mechanism as well as a virulence mechanism for bacterial pathogens. Bacterial adhesin is a media for bacteria to invade the host. Bacterial adhesin,is a medium for bacteria to invade the host. Baterial adhe-sion, moreover, is depend on the ligand interaction as a signaling mediator that will influence the invasion process and increase pro and anti-inflammatory due tob the influence of the receptors of innate immune response. Aggregatibacter actimycetemcomitans (A.actinomycetemcomitan) have many virulence factors that may result in tissue and alveolar bone damage. One of the virulence factors is adhesin that can be isolated from the fimbriae. This research purposed to analyze the ability of adhesin protein from A.actinomycetemcomitan that cause the destruction of alveolar bone. Thus, the number of osteoblasts and osteoclasts as well as osteocalcin expression can be used as a marker of damage on the alveolar bone of Wistar rats. The research was conducted through several processes. First, the adhesin of A.actinomycetemcomitan with a molecular weight (MW) of 24 kDa is induced into Wistar rats. Next, to determine the number of osteoblasts and osteoclasts performed, hematoxylin eosin staining is conducted. Meanwhile, to determine osteocalcin expression performed, immunohistochemical techniques is used. This research shows the decreasing of the number of osteoblasts and increasing of the number of osteoclasts in the treatment groups induced by adhesin proteins, A. actinomycetemcomitans + adhesin protein, and A.actinomycetemcomitan compared those in the control group. It also shows the increasing of osteocalcin expressions on the alveolar bone of Wistar rats in the groups induced by adhesin proteins, A. actinomycetemcomitans + adhesin protein, and A. actinomycetemcomitans than those in the control group. It can be concluded that the adhesin protein of A. actinomycetemcomitans plays an important role in the destruction of alveolar bone through the reduction of the number of osteoblasts, the increasing of the number of osteoclasts and oste-ocalcin expression in aggressive periodontitis.